Drivers’ Experiences of Traffic Police Corruption and the Implications for Governance Reform: Case Study of Madagascar’s National Police and Gendarmerie - Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire; Tsitaitse, Tahadray Jean; Marcel, Faharano; Bien-Aimé, Whega Danitsaike (Jurnal Pemerintahan dan Politik, 2025)
This study explores drivers’ experiences of traffic police corruption in Madagascar, focusing on operations within the National Police and Gendarmerie. Using qualitative research methods, the study conducted in-depth semi-structured interviews with 30 drivers from diverse socio-economic backgrounds who regularly interacted with traffic authorities in urban and rural regional in Madagascar. The interviews aimed to explore drivers’ perceptions, personal experiences, and coping strategies for navigating traffic encounters caused by corruption. The results indicate that drivers face frequent bribery demands from traffic police, especially in cases of minor infractions, where bribery is considered an effective means to avoid legal penalties. The study also highlights the role of power dynamics and lack of accountability in these corrupt practices. Informal networks of drivers and police contribute to a cycle of mutual reinforcement. Drivers’ responses also reveal a widespread erosion of trust in both the national police and gendarmerie, which are seen as a barrier to effective policing and public safety. The study underscores the need for reform of law enforcement practices, enhanced oversight, increased public awareness, and highlighting the critical role of the government in reducing corruption and improving traffic law enforcement in Madagascar.